Making design theory - Redstrèom, Johan (Cambridge, Massachusetts The MIT Press, 2017)
"Tendencies toward "academization" of traditionally practice-based fields have forced design to articulate itself as an academic discipline, in theoretical terms. In this book, Johan Redstrom offers a new approach to theory development in design research--one that is driven by practice, experimentation, and making. Redstrom does not theorize from the outside, but explores the idea that, just as design research engages in the making of many different kinds of things, theory might well be one of those things it is making. Redstrom proposes that we consider theory not as stable and constant but as something unfolding -- something acted as much as articulated, inherently fluid and transitional. Redstrom describes three ways in which theory, in particular formulating basic definitions, is made through design: the use of combinations of fluid terms to articulate issues; the definition of more complex concepts through practice; and combining sets of definitions made through design into "programs." These are the building blocks for creating conceptual structures to support design. Design seems to thrive on the complexities arising from dichotomies: form and function, freedom and method, art and science. With his idea of transitional theory, Redstrom departs from the traditional academic imperative to pick a side -- theory or practice, art or science. Doing so, he opens up something like a design space for theory development within design research." -- Publisher's descriptio
Thing and theory -- Tactics -- Between -- Making definitions -- Programs -- Presenting -- Transitional theory
Includes bibliographical references (pages 155-164) and index
Keywords: Design -- Philosophy